D&D text based captcha logic question in web services - Tan, Kia Him (2014)
The research discusses on the CAPTCHA, A CAPTCHA is an acronym for "Completely Automated Public Turing test to tell Computers and Humans Apart" to differentiate human from machine. In the previous condition, there are many types of CAPTCHA that implemented in the web. For example, text based, audio based, image based and puzzle based CAPTCHA. In this project, a drag and drop (D&D) text-based CAPTCHA will be develop for a better approach to CAPTCHA, text-based CAPTCHA using a simple logic question with a drag and drop feature for validation. Drag and drop is a pointing device gesture which user selects a virtual object by "grabbing" it and dragging it to a different place. The CAPTCHA will be created in web based application in web services using nuSoap library.